FEATURES OF DEVELOPMENT OF THE ADVOCACY INSTITUTE IN THE THIRD REPUBLIC OF ARMENIA - Harutyunyan, Nelli (State and Law, 2021)
The article discusses the development of the advocacy institute in the third Republic of Armenia. The article talks about the achievements in the field of advocacy, about the guarantees and principles prescribed by law and international documents necessary for advocacy.The article discusses the conditions that are necessary for the effective activities of advocate, the guarantees that are necessary for activities of advocate, arises the existing problems. The article talks about the necessary measures which should be taken by the state to ensure guarantees for the activities of advocate.
Keywords: Keywords - advocate, activities of advocate, the guarantees necessary for activities of advocate, independence of advocate, government interference in activities of advocate.